The role of christian religious education in strengthening youth morality in the era of social disruption - Benyamin Dadi Ratu Mofu (Indonesian Institute For Counseling, Education and Therapy, 2026)
The era of social disruption has significantly influenced youth morality through rapid technological advancement, globalization, and the widespread use of digital media. These changes have increased moral challenges, including ethical relativism, cyberbullying, misinformation, digital addiction, and declining social responsibility. This study aims to examine the role of Christian Religious Education in strengthening youth morality within this contemporary context. The research employed a library research approach using qualitative content analysis. Data were collected from scholarly books, peer-reviewed journals, theological literature, and relevant scientific publications concerning Christian Religious Education, youth morality, and social disruption. The findings indicate that Christian Religious Education contributes to moral development by fostering biblical values, spiritual maturity, ethical decision-making, digital responsibility, and character formation. Furthermore, effective moral education requires collaboration among schools, families, and churches to reinforce value internalization. The study concludes that Christian Religious Education remains a relevant and strategic framework for cultivating morally responsible, spiritually mature, and socially engaged youth capable of responding wisely to the challenges of an increasingly disruptive digital society.